Enhanced material, parts optimization and process intensification proceedings of the first International Joint Conference on Enhanced Material and Part Optimization and Process Intensification, Emporia 2020, May 19-20, 2020, Aachen, Germany - Drummer, Dietmar; Marschall, Holger; Reisgen, Uwe 1962- (Springer, 2021)
This book reports on topics at the interface between material processing, product and process optimization. It covers new developments and challenges in welding, brazing, cutting and coating, casting and molding, additive manufacturing, simulation and optimization techniques, as well as functional and structural materials and composites. Gathering authoritative contributions on the latest research and applications, presented at the International Joint Conference on Enhanced Material and Part Optimization and Process Intensification, EMPOrIA 2020, organized by SFB1120 Aachen, SFB814 Erlangen and CCE Darmstadt, on May 19–20, 2020, in Aachen, this book provides academics, students, and professionals with a timely snapshot of the main research trends, and extensive information on cutting-edge methods and technologies in materials, manufacturing and process engineering.